Microwave horns and feeds - Olver, A. D. (A. David); Clarricoats, P. J.; Kishk, A. A.; Shafai, L. (London, United Kingdom Institution of Electrical Engineers, 1994)
The following topics are dealt with: reflector antennas; radiation from apertures; numerical analysis using cylindrical and spherical waves in horns; numerical analysis of small axisymmetric feeds; pure-mode horns; prime-focus waveguide feeds; multimode horns; corrugated horns; dielectric-loaded horns; lens-corrected horns; dielectric feeds; dipole feeds; microstrip and resonator type feeds; and array feeds.
Electronic reproduction.
Keywords: Antennas, Reflector -- Design and construction; Antennas, Horn -- Design and construction; Antenna feeds -- Design and construction; Microwave communication systems -- Design and construction; Electronic books